Ecological vulnerability : the law and governance of human-wildlife relationships - Woolaston, Katie, 1983- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
Humans are responsible for biodiversity loss in many related and sometimes conflicting ways. Human-wildlife conflict, commonly defined as any negative interaction between people and wildlife, is a primary contributor to wildlife extinction and a manifestation of the destructive relationship that people have with wildlife. The author presents this 'wicked' problem in a social and legal context and demonstrates that legal institutions structurally deny human-wildlife conflict, while exacerbating conflict, promoting values consistent with individual autonomy, and ignoring the interconnected vulnerabilities shared by human and non-human species alike. It is the use of international and state law that sheds light on existing conflicts, including dingo conflict on K'Gari-Fraser Island in Australia, elephant conflict in Northern Botswana, and the global wildlife trade contributing to COVID-19. This book presents a critical analysis of human-wildlife conflict and its governance, to guide lawyers, scientists and conservations alike in the transformation of the management of human-wildlife conflict.
Introduction -- The human-wildlife relationship : an ecofeminist approach to vulnerability theory -- Friends in the wild? : the problem of human-wildlife conflict and its governance -- Friends in law? : the critical complexities of international wildlife law -- Human-dingo conflict on K'Gari-Fraser Island -- Human-elephant conflict in Northern Botswana -- Pandemic vulnerability and resilience : wildlife and COVID-19 -- Conclusion.
Title from publisher's bibliographic system (viewed on 13 Jun 2022).
Keywords: Wildlife conservation -- Law and legislation; Animals -- Law and legislation; Human-animal relationships